The Franks, the Martyrology of Usuard, and the Martyrs of Cordoba - Nelson, Janet L. (Studies in church history, 1993)
The bodies of holy martyrs, which the Romans buried with fire, and mutilated by the sword, and tore apart by throwing them to wild beasts: these bodies the Franks have found, and enclosed in gold and precious stones.For the author of the longer prologue to Lex Salica, writing in 763-4 in the reign of Pippin I, the first king of the Carolingian dynasty, the Franks’ devotion to the martyrs was the secret of their success. It proved the strength of their Christian faith; it was at once the manifestation and the explanation of special divine favour. Vivit qui Francos diligit Christus….